Somut olmayan kültürel mirasın müzecilik bağlamında korunması - Çankaya, Esra (My University, 2006)
ABSTRACT Today, specifically with the beginning of 50's, the gradual increase of technology andurbanization affect people's lives in various ways. With the reasons such as migration andindustrialization, the population between rural areas and cities naturally differ, thus, bothmiddle scaled cities and rising city centrums are enlarged at a great speed. With the changesin the process of globalization, the lives of people in the world have turned out to be stereo-typical. Physical, social, economic and psychological problems derived from the effect ofglobalization, demolish the intangible cultural assets known as ways and customs, traditionsand practices which date far back to the ancient times by shaping and also guiding the society. Therefore, safeguarding of this heritage has become much more crucial in the last years.Intangible cultural heritage which has been a subject of dispute especially in the last years,turned out to be a new study field in accordance with the suggestions including thesafeguarding both in the national and international arenas. The foremost reason for thisalteration is again globalization, with the process of globalization, societies genuine identitiesare at a risk while forming common effect and perspectives. As a result of this risk, the threatof a loss has become surely apparent and realized. The other reason which is worthmentioning is, the realization of the variegation and the vividness which may be theconsequence by eliminating the intolerance created by specific differences, hence, in theprocess of the communication not only within societies but also between distinct societies, theintangible assets which are not genuine will be safeguarded leading to the mentionedvariegation and vividness.In this specific study, the first section deals with the necessity of safeguarding the intangiblecultural heritage and its presence at the forefront by giving related examples. In the secondsection, tangible cultural heritage and intangible cultural heritage issues are discussed brieflyunder the subtitle of cultural heritage and the regulating factors of intangible cultural heritageare classified comprehensively. Regarding the third section, within the scale of multiculturismand by referring to the subtitle of cultural heritage, the effects of some cultural policies andglobalization on the cultural heritage are mentioned. The fourth section, including thesafeguarding of the intangible cultural heritage in the context of museology deals with severalstudies of national and international associations & institutions. Moreover, with these studies,a brief evaluation and summary of the outcomes are represented, the solutions related to the1concept of museology and the roles of museums in safeguarding the Intangible Cultural Heritage are clarified. In addition to these, the course of information between museum andsociety is clearly mentioned. In deed, the issue of safeguarding will deal with the answers ofthe questions which the actual study brings out.The study called "The Safeguarding of the Intangible Cultural Heritage Within The Context of Museology", is a research paper which literature and literal evaluation are involved,supported by field survey with focusing on factual data, its effects and benefits, surely cannot be ignored. Besides, the study is formalized -within the bounds of possibilities- in the fifthsection named as "MULTI-CULTURISM IN ISTANBUL, FESTIVES and SACRED DAYS",by signaling both written and oral documents, current studies, personal research andobservations. Activity will be actualized in Istanbul which is cultural center of Europe in 2010in Istanbul Archeology Museums. Last of all, in the sixth section an overall evaluation of thefinal situation takes place as well as with the related suggestions. Furthermore, the study called "The Safeguarding of the Intangible Cultural Heritage within the Context of Museology" is taken into consideration in the aspects of topical currency and topicaldevelopment and finalized by updating the further possible studies. Therefore, the study turnsout to be an absolute source opening new ways for further developments.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2006
Keywords: Somut Olmayan Kültürel miras; Kültür politikaları; ICOM